Cumulative prevalence of biological and social risk factors at birth in a city in São Paulo - da Cruz, Aline Adryane Morishigue Bássiga [UNESP]; Dos Santos, Lucas Cardoso [UNESP]; Minharro, Michelle Cristine de Oliveira; Aguiar Alencar, Rúbia [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to identify the cumulative prevalence of biological and social risk factors at birth. METHOD: a cross-sectional study, with retrospective data collection, carried out with live births in a medium-sized city, from January 2018 to July 2020. A database was used with information aimed at identifying social and biological risks after birth, assessed descriptively. RESULTS: the sample consisted of 4,480 newborns, of which 78.9% were classified as at usual risk, and 21.1% as at risk. The cumulative prevalence showed that most newborns had more than one risk factor, with biological risks being the most prominent: need for admission to Intensive Care Unit, birth with less than 37 weeks of gestation and weight less than 2,500 g. Among the social risks, the following stand out: newborns who had a dead sibling aged less than 5 years old; head of family without income; mothers under 16 years old and who did not undergo prenatal care. The biological risk rate was 7.39 times higher than the social risk rate. CONCLUSION: the cumulative prevalence of the risks found was significant, with a considerable part of the sample presenting some biological risk.